The Impact of Administrative Control Operations on Containment Strategies in Crisis Management: An Exploratory Study of the Opinions of a Sample of Heads of Administrative Units at the University of Sulaimani - صالح, صلاح حمه سعيد حمه (Sulaimani Journal for Humanities, 2025)
The main Objective of the study is to demonstrate the Impact of Administrative control on Containment Strategies in Crises Management at the University of Sulaimani. Stated the theoretical aspect and the fieldwork using statistical methods based on the statistical program (SPSS), The Structure of the study was divided into Four Sections, The First Section dealt with the methodology of the study. The Second Section covered the theoretical framework related to the subjects of administrative control and containment strategy in crisis management. The Third Section was the field side of the study. The hypotheses of the study were analyzed and the results obtained were collected by collecting data from the questionnaire distributed on 54 of the Holders of administrative positions in a group of colleges at the University of Sulaimani. The Researcher concluded his studies with the fourth Section presenting the main Conclusions from the study and Recommendations of the researcher, The most important conclusion of the study is the Relationship of the correlation and positive effect of the dimensions of administrative control processes from the University of Sulaimani on the dimensions of variable containment strategies in crises management consisting of ( detecting warning signals , Preparation and prevention, contain damage and restore activity ) , And researcher in one of his recommendations Recommends to Activate the Role of Administrative Controls on Government Institutio
Keywords: (Containment Strategies; Crisis management; Standards Supervision; ControlDeviations)